Automated thermal imaging monitors the local response to cervical cancer brachytherapy. Issue 1 (27th September 2022) - Hoffer, Oshrit; Rabin, Tatiana; Nir, Rony‐Reuven; Brzezinski, Rafael Y.; Zimmer, Yair; Gannot, Israel
Abstract: Malignant tumors have high metabolic and perfusion rates, which result in a unique temperature distribution as compared to healthy tissues. Here, we sought to characterize the thermal response of the cervix following brachytherapy in women with advanced cervical carcinoma. Six patients underwent imaging with a thermal camera before a brachytherapy treatment session and after a 7‐day follow‐up period. A designated algorithm was used to calculate and store the texture parameters of the examined tissues across all time points. We used supervised machine learning classification methods (K Nearest Neighbors and Support Vector Machine) and unsupervised machine learning classification (K‐means). Our algorithms demonstrated a 100% detection rate for physiological changes in cervical tumors before and after brachytherapy. Thus, we showed that thermal imaging combined with advanced feature extraction could potentially be used to detect tissue‐specific changes in the cervix in response to local brachytherapy for cervical cancer. Abstract : Malignant tumors have high metabolic and perfusion rates, which result in a unique temperature distribution as compared to healthy tissues. Here, we sought to characterize the thermal response of the cervix following brachytherapy in women with advanced cervical carcinoma. We showed that thermal imaging combined with advanced feature extraction could potentially be used to detect tissue‐specific changes in the cervix in response to local brachytherapy for cervical cancer.